Identifikasi Faktor Penyebab Pengembalian Berkas BPJS (Retur Claim) di Rumah Sakit Umum Dharma Yadnya Kota Denpasar Periode Triwulan IV Tahun 2023 - Wirawan, I Kadek Putra; Abadi, M. Fairuz; Sri Murcittowati, Putu Ayu (Poltekkes Kemenkes Jambi, 2025)
Background: Social Insurance Administration Organization (BPJS) has a crucial role in organizing social security programs in Indonesia. BPJS aims to ensure social protection for the community. BPJS is a legal entity that has a regulatory basis to regulate its operations. Claims are bills or demands for payment or health services provided to BPJS participants. This study aims to determine the factors causing the return of BPJS claim files at Dharma Yadnya General Hospital, Denpasar City. Method: The sample of this study was BPJS claim files totaling 137 claim files. The research data used by researchers is secondary data. The results of this study are the percentage of BPJS returns due to coding 30.65%, due to completeness 29.20%, due to visit indications 32.12%, and due to treatment indications 8.1%. These results were obtained from a total of 137 claim files returned by BPJS. Results: Based on the results of the study that has been carried out on the factors for returning BPJS claims at Dharma Yadnya General Hospital, it can be concluded that the largest factor in returning BPJS files is due to visit indications of 44 BPJS claim files. Conclusion: Socialization regarding coding standard rules, visit indications, treatment indications and completeness of medical record contents should be improved.